Achieving superior fatigue strength in a powder-metallurgy titanium alloy via in-situ globularization during hot isostatic pressing. (15th April 2023) - Guo, R.P.; Cheng, M.; Zhang, C.J.; Qiao, J.W.; Cai, C.; Wang, Q.J.; Xu, D.S.; Xu, L.; Yang, R.; Shi, Y.S.; Liaw, P.K.
Abstract: Powder-metallurgy (PM) titanium alloys exhibit outstanding quasistatic-mechanical properties, but suffer from low fatigue performance, which severely limits their applications in aerospace. Here, we achieve a superior fatigue strength of 600 MPa in a near- α PM titanium alloy, using a two-step hot-isostatic-pressing scheme, during which more than 80 vol.% (volume fraction) randomly orientated equiaxed grains was obtained. The largely improved fatigue strength (∼ 25%) is mainly attributed to the in - situ globularization of the lamella-like microstructure, leading to higher crack nucleation resistance and lower growth rates of short cracks. The present findings offer a useful route for fabricating PM titanium alloys with high fatigue strengths. Graphical abstract: Image, graphical abstract